Blood pressure alterations in burn patients with septic shock under hydro-cortisone treatment - Alinejad, Faranak (Iran J Microbiol, 2015)
BACKGROUND AND OBJECTIVES: Hydrocortisone is widely used in septic shock cases resistant to fluid and vasopressor therapy. It may result in increased blood pressure and survival. However the efficacy is no established among patients with severe burn and septic shock. Accordingly it was assessed in this study. MATERIALS AND METHODS: The patients older than 14 years of age with resistant septic shock were enrolled during one-year period. The hydrocortisone was prescribed 100 mg three times per day and the alterations in systolic and diastolic blood pressures were recorded. RESULTS: Twenty-nine patients were enrolled including 19 men and 10 women. The mean age was 37 ± 19 years and the mean burn surface area was 60 ± 20. Fourteen patients had positive blood culture. The most common isolated microorganism were Pseudomonas aeuroginosa in 34.6%(10 cases), and then Acinetobacter in 13.8%(4 cases). The infection was from wound in 79% and the remaining 21% had pneumonia. Twenty-one patients had good response to hydrocortisone and the increase in systolic and diastolic blood pressures was significant; but the mortality rate was similar. CONCLUSION: Treatment with hydrocortisone would result in increase in systolic and diastolic blood pressure in burn patients with resistant septic shock.